Percutaneous Transforaminal Endoscopic Discectomy Versus Microendoscopic Discectomy for Lumbar Disc Herniation: Two-Year Results of a Randomized Controlled Trial. Issue 8 (15th April 2020) - Chen, Zihao; Zhang, Liangming; Dong, Jianwen; Xie, Peigen; Liu, Bin; Wang, Qiyou; Chen, Ruiqiang; Shu, Tao; Li, Shangfu; Feng, Feng; Yang, Bu; He, Lei; et al.
Abstract : Study Design: A prospective randomized controlled study. Objective: To clarify whether percutaneous transforaminal endoscopic discectomy (PTED) has better clinical outcomes and less surgical trauma compared with microendoscopic discectomy (MED). Summary of Background Data: Two kinds of minimally invasive spine surgeries, PTED and MED, are now widely used for the treatment of lumbar disc herniation (LDH). It is still a controversial issue to choose the proper surgical approach. Methods: In this single-center, open-label, randomized controlled trial, patients were included if they had persistent signs and symptoms of radiculopathy with corresponding imaging-confirmed LDH, and were randomly allocated to PTED or MED group. The primary outcome was the score of Oswestry Disability Index (ODI) and the secondary outcomes included the score of Medical Outcomes Study 36-Item Short-Form Health Survey bodily pain and physical function scales, European Quality of Life-5 Dimensions, and Visual Analogue Scales for back pain and leg pain. Results: A total of 250 participants were randomly assigned to two treatment groups, 241 of that received the specific surgical procedure. Two hundred twenty-two patients (92.1%) have completed the 2-year follow-up. Both the primary and secondary outcomes did not differ significantly between the two treatment groups at each prespecified follow-up time ( P  > 0.05). For PTED, the postoperative improvement of ODI score in the median herniation subgroup was less compared with paramedian subgroup. For MED, less improvement of ODI score was found in far-lateral herniation subgroup compared with paramedian subgroup. Total complication rate over the course of 2 year was 13.44% in PTED group and 15.57% in MED group ( P  = 0.639). Ten cases (8.40%) in PTED group and five cases (4.10%) in MED group suffered from residue/recurrence of herniation, for which reoperation was required. Conclusion: Over the 2-year follow-up period, PTED did not show superior clinical outcomes and did not appear to be safer procedure for patients with LDH compared with MED. PTED had inferior results for median disc herniation, whereas MED did not appear to be the best option for far-lateral disc herniation. Level of Evidence: 2 Abstract : This article aimed to clarify whether percutaneous transforaminal endoscopic discectomy (PTED) has better clinical outcomes compared with microendoscopic discectomy (MED) for the treatment of lumbar disc herniation. PTED did not show superior clinical outcomes and safety compared with MED over the 2-year follow-up period. PTED seemed to be inferior for median disc herniation, whereas MED seemed to be a nonoptimal option for far-lateral disc herniation.